The effects of native and modified clupeine on the structure of gram-negative model membranes. (October 2019) - English, M.; Paulson, A.; Green, R.J.; Florek, O.; Clifton, L.A.; Arnold, T.; Frazier, R.A.
Graphical abstract: Highlights: The magnitude of the structural changes observed in the models studied was greater in the presence of modified vs. native protamine. Simultaneous fitting of neutron reflectometry and x-ray reflectometry data resulted in surface excess estimates for both peptides. Thickening of peptide layers may be attributed to improved hydrophobicity and electrostatic interactions with lipid head groups in the models. Overall, reducing the charge on the native peptide changes the way in which the modified peptide disrupts the model membranes studied. Abstract: Clupeine, a cationic antimicrobial peptide found in fish, is of interest as a food additive but non-specific binding of the peptide to anionic molecules reduces its antimicrobial activity. The overall positive charge of clupeine can be reduced by blocking 10% of its arginine residues with 1, 2-cyclohexanedione (CHD). The modified peptide retains antimicrobial activity but it is not known if its effect on the structure of Gram-negative model membranes is the same as the native peptide. In the presented paper, neutron reflectometry (NR) and X-ray reflectometry were used to investigate the effect of native and modified clupeine on the structure of model monolayer membranes composed of Phosphatidylethanolamine (PE), Phosphatidylglycerol (PG), and Cardiolipin (CL). The effect of the peptides on the structure of 1, 2-dipalmitoyl (d62)-sn-glycero-3-phosphocholine (DPPC)/PE:PG:CL bilayers were also examined by NR. In both model systems, modified clupeine demonstrated a greater effect on the lipid structure. Charge reduction in the modified sample also resulted in improved hydrophobicity, and the formation of thicker peptide layers in the membrane models. Some lipid translocation was observed in the inner tail region (∼69 ± 0.24% DPPC and ∼24 ± 0.02% PE:PG:CL); and in the outer tail region (∼24 ± 0.02% DPPC and ∼56 ± 0.01% PE:PG:CL). Improved hydrophobicity and electrostatic interactions with lipid head groups, strongly suggests that the modified clupeine may use the carpet mechanisms to exert its effect on model membranes. These findings suggest that changing the charge on the native peptide changes the way in which the modified peptide disrupts Gram-negative model membranes.